Policy for play : responding to children's forgotten right / Adrian Voce. - Voce, Adrian (Policy Press, 2015)
Using the UK government's play strategy for England (2008-10) as a case study, this is the first book to look in detail at children's play within public policy. It is an essential tool for practitioners and campaigners around the world.